Influence of nutrition on the virulence and stability of the insect-pathogenic fungus Metarhizium anisopliae. - Syed Farooq Abbas Shah (2004)
Nutrition influenced growth, sporulation, phenotypic stability and virulence of the insect pathogenic fimgus, Metarhizium anisopliae. Virulent conidia were produced on nutrient poor or osmotic stress media, while least virulent conidia were produced on nutrient rich media. Repeated subculturing on nutrient rich media caused further attenuation of virulence, however, attenuation was strain dependant. Several strain independent parameters were identified that could be used to monitor the virulence of M anisopliae conidia during normal production or when developing new inexpensive culture media. Virulent conidia typically had high levels of spore bound Prl, a CN ratio below 5.2:1 and high germination rates. RT-PCR revealed that virulent conidia from insects contained high levels of transcripts of prl A and other pathogenicity-related genes (e.g. ste 1, try 1 and chy 1). Virulent conidia from 1% yeast extract media had higher levels of transcripts of these pathogenicity-related genes than the least virulent conidia from CN 35:1 medium (= SDA), however, levels were significantly lower than those in insect-derived conidia. This study shows for the first time that passaged inoculum is virulent irrespective of the original culture medium or insect host suggesting that starvation conditions, whether in vivo or in vitro, results in de-repression of Prl and that elevated levels of this enzyme enhance fungal virulence. Nutrition also influenced expression of other pathogenicity determinants e.g. adhesive properties of conidia (hydrophobicity, surface charge) and destruxins production, however, inconclusive relationship between these pathogenicity determinants and nutrition was observed. Nutrition also influenced fungal stability independent of strain. Under similar nutritional conditions, V275 produced fewer sectors than V245. Most sectors were sterile and produced significantly lower quantities of pathogenicity determinants. Careful selection of stable strains and manipulation of cultural conditions could be employed to enhance or stabilize virulence of M anisopliae.